The Economic Progress of the Ottoman Empire: An Analysis of Advancement During the Reign of Sultan Suleiman the Magnificent - Putra, Johan Septian; Rahmi, Zakiyah (Regalia Institute, 2024)
The development of the Islamic economy during the reign of Suleiman al-Qanuni (1520–1566 CE) represents one of the significant episodes in the history of global economic development. This article analyzes the economic progress achieved by the Ottoman Empire during the reign of Sultan Suleiman the Magnificent (1520-1566), known as one of the peak periods in the empire's history. The main focus of this research is on the economic policies implemented by Sultan Suleiman, as well as their impact on key sectors such as agriculture, trade, and taxation. The research methods employed are: heuristics, source criticism, interpretation, and historiography. The research findings indicate that Suleiman's reign saw the implementation of reforms in the administrative and tax systems, including the continuation of the timar system, which contributed to a more equitable distribution of resources and increased agricultural output. Furthermore, rapidly growing trade relations with Europe, Asia, and Africa positioned the Ottoman Empire as a global trade center, which significantly benefited the economy. Overall, the reign of Sultan Suleiman played a crucial role in modernizing and strengthening the Ottoman economic structure through constructive and systematic policies, bringing prosperity to its people during the 16th century.